Academic Integrity in Canada An Enduring and Essential Challenge - Eaton, Sarah Elaine; Christensen Hughes, Julia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book presents original contributions and thought leadership on academic integrity from a variety of Canadian scholars. It showcases how our understanding and support for academic integrity have progressed, while pointing out areas urgently requiring more attention. Firmly grounded in the scholarly literature globally, it engages with the experience of local practicioners. It presents aspects of academic integrity that is specific to Canada, such as the existence of an "honour culture", rather than relying on an "honour code". It also includes Indigenous voices and perspectives that challenge traditional understandings of intellectual property, as well as new understandings that have arisen as a consequence of Covid-19 and the significant shift to online and remote learning. This book will be of interest to senior university and college administrators who are interested in ensuring the integrity of their institutions. It will also be of interest to those implementing university and college policy, as well as those who support students in their scholarly work.
Section I: Understanding the big picture of academic integrity in Canada: An Enduring Challenge -- Section introduction: Understanding the big picture of academic integrity in Canada -- Academic integrity in Canada: A historical perspective and current trends -- Integrity violations in the academy: A decade of growing complexity and concern (2010-2020) -- Confronting COVID-19: What the pandemic taught us about academic integrity -- Academic integrity through a SoTL Lens and 4M Framework: An institutional self-study -- An administrator$1 (Bs perspectives of the academic misconduct ecosystem: recommendations for resolving multi-stakeholder differences -- Re-defining academic Integrity with Indigenous truths -- Accountability, relationality and Indigenous epistemology: Advancing an Indigenous perspective on academic integrity -- Understanding provincial and territorial academic integrity policies for elementary and secondary education in Canada -- Section II: Understanding academic integrity in specific contexts -- Section introduction: Understanding academic integrity in specific contexts -- Academic integrity in Canadian engineering schools -- Teaching the teachers: Do preservice teachers plagiarise? -- Visual plagiarism: Seeing the forest and the trees -- The distinctive nature of academic integrity in graduate legal education -- Perceptions and experiences in understanding academic integrity: Reflections within a doctoral program -- The barriers to reporting incidences of academic dishonesty: The unique perspective of faculty from Canadian community colleges -- Promotion of academic integrity through a marketing lens for Canadian post-secondary institutions -- Academic integrity in the practice / service learning setting -- Promoting academic integrity and preventing misconduct in a Canadian open digital distance education university -- Section III: An urgent and growing problem: Contract cheating in Canada -- Section introduction: Contract cheating in Canada -- Ethics, ed tech, and therise of contract cheating -- Pay-to-pass: Knowledge as a commodity in the digital age -- Education as a financial transaction: Contract employment and contract cheating -- Committing and facilitating academic misconduct as white-collar and corporate crime -- Section IV: Essential strategies and levers to advance academic integrity -- Section introduction: Essential strategies and levers to advance academic integrity -- Using quality assurance frameworks to support an institutional culture of academic integrity at Canadian universities -- Beyond the traditional: Academic integrity advocacy in Canadian librarianship -- Using computer-facilitated focus groups to gather student insight on academic integrity -- Fostering academic integrity through curriculum design -- Threading the needle: Student advocacy offices and their role within academic integrity -- Helping students resolve the ambiguous expectations of academic integrity -- How to talk about academic integrity, so students will listen: The inherent challenge in (3z(Bmandated(3y (Btraining -- Revisioning instructor-writing specialist collaboration for paraphrasing instruction -- Supporting academic integrity in the writing centre: Student consultant perspectives -- Cultural aspects of academic integrity -- A new framework for enhancing (academic) integrity -- Building a culture of restorative practice and restorative responses to academic misconduct.s
Keywords: Education, Higher; Education and state; School management and organization; School administration; Higher Education; Educational Policy and Politics; Organization and Leadership